Efficient mechanochemical synthesis of regioselective persubstituted cyclodextrins - Jicsinszky, Laszlo; Caporaso, Marina; Martina, Katia; Calcio Gaudino, Emanuela; Cravotto, Giancarlo (Beilstein Journal of Organic Chemistry, 2016)
A number of per-6-substituted cyclodextrin derivative syntheses have been effectively carried out in a planetary ball mill under solvent-free conditions. The preparation of Bridion® and important per-6-amino/thiocyclodextrin intermediates without polar aprotic solvents, a source of byproducts and persistent impurities, could be performed. Isolation and purification processes could also be simplified. Considerably lower alkylthiol/halide ratio were necessary to reach the complete reaction in comparison with thiourea or azide reactions. While the presented mechanochemical syntheses were carried out on the millimolar scale, they are easily scalable.
Keywords: green chemistry; nucleophilic substitution; planetary ball mill; siRNA delivery intermediate; sugammadex

Cyclodextrin Chemistry. Reactivity and Structure: Concepts in Organic Chemistry - Bender, M. L.; Komiyama, M. (Springer, 1978)

Cyclodextrins and Their Inclusion Complexes - Szejtli, J. (Akadémiai Kiadó, 1982)

Cyclodextrins. Comprehensive Supramolecular Chemistry - Szejtli, J.; Oda, T. (Pergamon, 1996)

(untitled) - Astier, Y.; Braha, O.; Bayley, H. (J. Am. Chem. Soc., 2006)

(untitled) - Sanderson, K. (Nature, 2008)

(untitled) - Gooding, M.; Malhotra, M.; McCarthy, D. J.; Godinho, B. M. D. C.; Cryan, J. F.; Darcy, R.; O’Driscoll, C. M. (Eur. J. Pharm. Sci., 2015)

(untitled) - Zhang, M.-Q. (Drug Discovery Today: Technol., 2010)

(untitled) - Rojas, M. T.; Koeniger, R.; Stoddart, J. F.; Kaifer, A. E. (J. Am. Chem. Soc., 1995)

(untitled) - Martina, K.; Rinaldi, L.; Baricco, F.; Boffa, L.; Cravotto, G. (Synlett, 2015)

(untitled) - Rinaldi, L.; Binello, A.; Stolle, A.; Curini, M.; Cravotto, G. (Steroids, 2015)

(untitled) - Cravotto, G.; Caporaso, M.; Jicsinszky, L.; Martina, K. (Beilstein J. Org. Chem., 2016)

(untitled) - Vizitiu, D.; Walkinshaw, C. S.; Gorin, B. I.; Thatcher, G. R. J. (J. Org. Chem., 1997)

(untitled) - Gadelle, A.; Defaye, J. (Angew. Chem., Int. Ed. Engl., 1991)

(untitled) - Khan, A. R.; D’Souza, V. T. (J. Org. Chem., 1994)

(untitled) - Bom, A.; Bradley, M.; Cameron, K.; Clark, J. K.; van Egmond, J.; Feilden, H.; MacLean, E. J.; Muir, A. W.; Palin, R.; Rees, D. C.; Zhang, M.-Q. (Angew. Chem., 2002)

(untitled) - Wu, T.; Liu, Z.; Guo, Y.; Dong, C. (J. Electroanal. Chem., 2015)

(untitled) - Stolle, A.; Szuppa, T.; Leonhardt, S. E. S.; Ondruschka, B. (Chem. Soc. Rev., 2011)

(untitled) - Beyer, M. K.; Clausen-Schaumann, H. (Chem. Rev., 2005)

Comprehensive Organic Synthesis - Hernández, J. G.; Avila-Ortiz, C. G.; Juaristi, E. (Useful Chemical Activation Alternatives in Solvent-Free Organic Reactions, 2014)

Ball Milling Towards Green Chemistry - Ranu, B. C.; Chatterjee, T.; Mukherjee, N. (Carbon–Heteroatom Bond Forming Reactions and Heterocycle Synthesis under Ball Milling, 2014)

(untitled) - Jicsinszky, L.; Caporaso, M.; Tuza, K.; Martina, K.; Calcio Gaudino, E.; Cravotto, G. (ACS Sustainable Chem. Eng., 2016)

(untitled) - Menuel, S.; Doumert, B.; Saitzek, S.; Ponchel, A.; Delevoye, L.; Monflier, E.; Hapiot, F. (J. Org. Chem., 2015)

(untitled) - Matsui, Y.; Ono, M.; Tokunaga, S. (Bull. Chem. Soc. Jpn., 1997)

(untitled) - Rohrbach, R. P.; Rodriguez, L. J.; Eyring, E. M.; Wojcik, J. F. (J. Phys. Chem., 1977)

(untitled) - Uccello-Barretta, G.; Evangelisti, C.; Balzano, F.; Vanni, L.; Aiello, F.; Jicsinszky, L. (Carbohydr. Res., 2011)

(untitled) - Adam, J. M.; Bennett, D. J.; Bom, A.; Clark, J. K.; Feilden, H.; Hutchinson, E. J.; Palin, R.; Prosser, A.; Rees, D. C.; Rosair, G. M.; Stevenson, D.; Tarver, G. J.; et al. (J. Med. Chem., 2002)

(untitled) - Mazzaglia, A.; Donohue, R.; Ravoo, B. J.; Darcy, R. (Eur. J. Org. Chem., 2001)

(untitled) - Eccles, K. S.; Elcoate, C. J.; Lawrence, S. E.; Maguire, A. R. (ARKIVOC, 2010)

(untitled) - Mochida, K.; Kagita, A.; Matsui, Y.; Date, Y. (Bull. Chem. Soc. Jpn., 1973)